Assessing Polycyclic Aromatic Hydrocarbons (PAHs) using passive air sampling in the atmosphere of one of the most wood-smoke-polluted cities in Chile: The case study of Temuco. (September 2015) - Pozo, Karla; Estellano, Victor H.; Harner, Tom; Diaz-Robles, Luis; Cereceda-Balic, Francisco; Etcharren, Pablo; Pozo, Katerine; Vidal, Victor; Guerrero, Fabián; Vergara-Fernández, Alberto
Highlights: PAHs were measured in one of the most wood-smoke-polluted cities in Chile. PAH highest levels were detected in the winter season in Temuco. Residential wood combustion has a strong influence on PAH levels. Agreement between PAH levels and profiles in active and passive samples was detected. PUF disk is useful for tracking the effectiveness of pollution control measures in urban areas. Abstract: This study addresses human health concerns in the city of Temuco that are attributed to wood smoke and related pollutants associated with wood burning activities that are prevalent in Temuco. Polycyclic Aromatic Hydrocarbons (PAHs) were measured in air across urban and rural sites over three seasons in Temuco using polyurethane foam (PUF) disk passive air samplers (PUF-PAS). Concentrations of ΣPAHs (15 congeners) in air ranged from BDL to ∼70 ng m −3 and were highest during the winter season, which is attributed to emissions from residential heating by wood combustion. The results for all three seasons showed that the PAH plume was widespread across all sites including rural sites on the outskirts of Temuco. Some interesting variations were observed between seasons in the composition of PAHs, which were attributed to differences in seasonal point sources. A comparison of the PAH composition in the passive samples with active samples (gas + particle phase) from the same site revealed similar congener profiles. Overall, the study demonstrated that the PUF disk passive air sampler provides a simple approach for measuring PAHs in air and for tracking effectiveness of pollution control measures in urban areas in order to improve public health.